Kritik Hadis dalam Perspektif Sejarawan - Afwadzi, Benny (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
This article aims to elaborate methodological investigation of ḥadîth criticism of the historians point of view. It also observes the salient differences between them and the scholars of ḥadîth, as both are often on different worldview. Through descriptive-analytical study, the author comes to the conclusion that there are at least two methods of ḥadîth criticism in historian perspective that are [1] critical in analysing the companions of the Prophet and [2] critical to the content (matn) of ḥadîth. By shifting paradigm framework, it suggests that both of them should not be rejected. Both perspectives should be used as a method to develop the tradition of ḥadîth criticism, although at some points, they have to be put on critical consideration. On the other side, the historian perspective might be useful to encourage the weaknesses which has been existed in conventional science of ḥadîth criticism.